2022
DOI: 10.1021/acs.langmuir.2c00532
|View full text |Cite
|
Sign up to set email alerts
|

Robust Superamphiphobic Fabrics with Excellent Hot Liquid Repellency and Hot Water Vapor Resistance

Abstract: Superamphiphobic surfaces progress rapidly but suffer from the issues of low repellency to hot liquids, complicated and nonaqueous preparation methods, and low durability. Here, a simple waterborne approach is developed to fabricate robust superamphiphobic fabrics with excellent hot liquid repellency and hot water vapor resistance. First, a perfluorodecyl polysiloxane (FD-POS) aqueous suspension was prepared by hydrolytic cocondensation of (3-glycidyloxy propyl)­trimethoxysilane and 1H,1H,2H,2H-perfluorodecylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…However, photothermal conversion materials face serious rainwater corrosion and environmental pollutant pollution problems during long-term outdoor operation, which significantly affects their performance stability and service life. Meanwhile, the superhydrophobic surface with a water contact angle (WCA) larger than 150° and sliding hysteresis angle less than 10° can possess the self-cleaning ability against rainwater and contaminants. Therefore, combining the superhydrophobic coatings with photothermal conversion materials to fabricate a flexible photothermal superhydrophobic material is able to meet the requirement of real applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, photothermal conversion materials face serious rainwater corrosion and environmental pollutant pollution problems during long-term outdoor operation, which significantly affects their performance stability and service life. Meanwhile, the superhydrophobic surface with a water contact angle (WCA) larger than 150° and sliding hysteresis angle less than 10° can possess the self-cleaning ability against rainwater and contaminants. Therefore, combining the superhydrophobic coatings with photothermal conversion materials to fabricate a flexible photothermal superhydrophobic material is able to meet the requirement of real applications.…”
Section: Introductionmentioning
confidence: 99%
“…The as-formed homogeneous F-silica suspension is mainly composed of silicone oligomers and oligomer-modified silica nanoparticles. Then, the PET and stretched PET fabrics were immersed in the suspension for 10 min, during which F-silica was adsorbed onto the fabric microfibers by hydrogen bonding between their Si–OH/–OH groups . Subsequently, the fabrics were dried at 60 °C for 2 h to fix F-silica on the microfibers, and then the stretched fabrics were released to form micro-/nanostructures on the microfibers.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the PET and stretched PET fabrics were immersed in the suspension for 10 min, during which F-silica was adsorbed onto the fabric microfibers by hydrogen bonding between their Si−OH/−OH groups. 47 Subsequently, the fabrics were dried at 60 °C for 2 h to fix F-silica on the microfibers, and then the stretched fabrics were released to form micro-/nanostructures on the microfibers. Finally, all the fabrics were cured at 140 °C for 4 h to strengthen bonding of the micro-/nanostructures on the microfibers by further condensation of the silicone oligomers and with the microfibers.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…In addition, waterborne SHB fabrics have also shown important applications in scald prevention, pressure resistance and heat resistance. [164][165][166] For example, Zhang's research group 165 reported a waterborne SHB fabric for efficient scaldprevention by dip-coating the fabric in a hexadecyl polysiloxane (HD-POS) aqueous suspension. The obtained fabric could efficiently prevent the penetration of hot water and most of the steam, thus avoiding the direct contact of hot water and steam with the rat skin.…”
Section: Other Potential Applicationsmentioning
confidence: 99%